SUMOylation Attenuates the Function of PGC-1α - Rytinki, Miia M. (American Society for Biochemistry and Molecular Biology, 2009)
Peroxisome proliferator-activated receptor γ-coactivator-1α (PGC-1α) is a key coordinator of gene programs in metabolism and energy homeostasis in mammals. It is highly responsive to changes in the cellular environment and physiological status of mammals and regulated by post-translational modifications: acetylation, phosphorylation, and methylation. Here, we show that PGC-1α is covalently modified by small ubiquitin-like modifier (SUMO) 1 protein, an important regulator of signaling and transcription. Conserved lysine residue 183 located in the activation domain of PGC-1α was identified as the major site of SUMO conjugation. Interestingly, the same Lys residue is also a target for acetylation. Therefore, the E185A mutation disrupting the SUMOylation consensus sequence was utilized to show that SUMOylation plays a role in the regulation of PGC-1α function. Our results show that SUMOylation does not have an apparent effect on the subcellular localization or the stability of PGC-1α, but it attenuates the transcriptional activity of the coactivator, probably by enhancing the interaction of PGC-1α with corepressor RIP140. Mutation that abolished the SUMOylation augments the activity of PGC-1α also in the context of PPARγ-dependent transcription. Thus, our findings showing that reversible SUMOylation can adjust the activity of PGC-1α add a novel layer to the regulation of the coactivator.